Model of Human Resources Management (HRM) Practices Factors Affecting Small and Medium Enterprises (SMEs) Performance - Al Qaydi, Ebrahim Matar Salem; Aris, Amir (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a development of Structural Equation Model (SEM) that shows the relationship of human resource management (HRM) practices and the factors affecting the organizational performance of small and medium enterprises (SMEs) in UAE. The model comprises five independent constructs of HRM practices factors and one dependent construct of SME organizational performance. Constructs of Independent Variables (IV) contain 36 items/factors and the construct of the dependent variable (DV) contains ten items/factors. The data used to develop the model was gathered through a questionnaire survey amongst SMEs human resources personnel from several SMEs in UAE. A total of 226 questionnaire forms were collected and analysed with the response rate of 88.7%, which is considered a good representation of the sample size. The developed model was analysed and assessed with AMOS-SEM software at measurement and structural levels to ensure that both levels achieve the fitness criteria. After the structural model achieved the satisfactory level of goodness of fit. The model was evaluated using path analysis to determine the relationship between IV and DV. It was found that all the IVs are significant to DV. Hence, the model has demonstrated the multivariate relationship between the considered variables/factors related to the topic of this paper. The findings can assist the practitioners in SMEs organizations in planning and implementing.